(α, β, γ) - derivations of diassociative algebras - Fiidow, Mohamed Abubakar Hagi Mohamed; Rakhimov, Isamiddin Sattarovich; Said Husain, Sharifah Kartini; Basri, Witriany (Institute for Mathematical Research, Universiti Putra Malaysia, 2016)
In this research we introduce a generalized derivations of diassociative algebras and study its properties. This generalization depends on some parameters. In this paper we specify all possible values of the parameters. We also provide all the generalized derivations of low-dimensional complex diassociative algebras.